Post Effect of 73rd Amendment on Women Representation in Panchayat of NE India - Chatterjee, Rajesh; Debnath, Naigopal (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Panchayat being local self-government, is a state matter and part of the list of States in the Seventh Schedule of the Constitution of India. Article (3) of Article 243D of the Constitution ensures the participation of women in Panchayati Raj Institutions so that not less than one-third of the total seats filled through direct elections and the number of offices of the Chairperson of Panchayats are reserved for women. The 73rd amendment is the tool to reinsure women representation in the PRIs. There is a good relation between women and development of society. Again, development of women means advancement of the populace and the country. So there is a need to observe the actual status of the panchayat in relation to the women representation as per the mandate of the Constitution. An initiative has been taken to make known the actual impact of the amendment on women as well as society.